Role of prognostic factors in understanding disease severity in COVID-19 patients: Pakistan ordinance factories Hospital experience - Rifat Yasmin; Huma Hussain; Syeda Turab Fatima Abidi; Syed Asim Ali Shah; Lubna Ghazal; Tazaeen Hina Kazmi (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Coronavirus disease (COVID-19) is an emerging public health challenge. Study was conducted to determine the association of prognostic factors with disease severity in COVID-19 patients at POF Hospital, Wah Cantt. We conductedadescriptivecross-sectional study at a department of Medicine, POF Hospital, Wah Medical College (affiliated with National University of Medical Sciences) Wah Cantt. METHODOLOGY: We calculateda sample size of 158 patients (WHO Calculator). The study duration was 6 months (November 2020-April 2021).The selection of COVID patients was done through non probability sampling (consecutive). Respiratory sample for all participating patients were collected (from throat or sputum). These samples were tested for SARS-CoV-2 using WHO standard. SPSS version 24 was utilized for data analysis purpose. Chi square test and independent t-test were applied. Logistic regression was applied. RESULTS:Total data consist of 158 patients with COVID-19. Mean age of patients was52.3±3.26 years. Total leukocytes count (p=0.02), absolute neutrophil count (p=0.000), C reactive protein (p=0.000), NLR (p=0.03) were comparatively greater in patients with Severe COVID-19. While absolute lymphocyte were significantly lower in severe COVID-19 patients as compared to non-severe (p=0.03). Age[OR, 1.06 ;95% CI (1.027-1.114);p=0.01], diabetes mellitus[OR, 0.281 ;95% CI (0.100-0.788) p=0.016 and Hypertension [OR, 3.045 ;(1.044-8.878)95% CI p=0.04] are significant predictors of COVID-19 severity CONCLUSION:Prognostic factors of COVID-19 increased the likelihood of disease progression. C reactive protein andALC were significant predictors of COVID-19.